Hierarchically Porous ZSM-5 Synthesized by Nonionic- and Cationic-Templating Routes and Their Catalytic Activity in Liquid-Phase Esterification - Rino R. Mukti; Y. Kamimura; W. Chaikittisilp; H. Hirahara; A. Shimojima; M. Ogura; K. K. Cheralathan; S. P. Elangovan; K. Itabashi; T. Okubo (Journal of Mathematical and Fundamental Sciences, 2011)
Hierarchically porous MFI zeolites (ZSM-5) have been synthesized by hydrothermal treatment in the presence of trialkoxysilylated-derivatives of nonionic poly(oxyethylene) alkyl ether or alkyl quaternary ammonium cation as mesopore-generating agent, along with tetrapropylammonium cation as zeolite structure-directing agent. Powder X-ray diffraction revealed that zeolites have been crystallized, and scanning electron microscopy showed rugged surface morphology that was quite different from conventional ZSM-5. The mesoporosity was confirmed by nitrogen adsorption-desorption measurement showing type IV isotherms with narrow distribution of mesopore diameters. The catalytic activity of these mesoporous ZSM-5 was tested in liquid-phase esterification of benzyl alcohol with hexanoic acid. The conversion of benzyl alcohol on mesoporous ZSM-5 prepared via cationic-templating route was almost 100%, being much higher than on mesoporous ZSM-5 prepared with silylated nonionic surfactant as well as on conventional ZSM-5 with no mesopores. The presence of BrÃ¸nsted acid sites, together with the mesopores, was responsible for this catalytic conversion, as confirmed by pyridine adsorption monitored by in situ infrared and 27Al magic angle spinning nuclear magnetic resonance spectroscopy.